2019
DOI: 10.1142/s0219467819500189
|View full text |Cite
|
Sign up to set email alerts
|

Effective Descriptors for Human Action Retrieval from 3D Mesh Sequences

Abstract: Two novel methods for fully unsupervised human action retrieval using 3D mesh sequences are presented. The first achieves high accuracy but is suitable for sequences consisting of clean meshes, such as artificial sequences or highly post-processed real sequences, while the second one is robust and suitable for noisy meshes, such as those that often result from unprocessed scanning or 3D surface reconstruction errors. The first method uses a spatio-temporal descriptor based on the trajectories of 6 salient poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Most of these methods learn motion features from RGB-D image sequences. The work of Veinidis et al 7 proposes to construct a spherical histogram using the 3D position of the joint. After reprojecting and clustering into a vocabulary using LDA, the encoded features are fed to a hidden Markov model (HMM) for classification.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods learn motion features from RGB-D image sequences. The work of Veinidis et al 7 proposes to construct a spherical histogram using the 3D position of the joint. After reprojecting and clustering into a vocabulary using LDA, the encoded features are fed to a hidden Markov model (HMM) for classification.…”
Section: Introductionmentioning
confidence: 99%
“…But the analysis found that the score rate and usage rate are not proportional. It shows that there are still problems that need to be improved and improved in the teaching and training of whipping [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Figure 3 clearly evidences that the 3D human with similar poses belong to very close distributions. These results show the assumption that given a = 0, λ = 0, c = 1 (normal field L 2 metric), the metric is preserved under shape change, and could be used in pose and motion analysis application [18,28]. The figure 4 shows that 3D human with similar shape belong to very close distribution.…”
Section: Experiments 71 Assessment Of the Family Of Elastic Metricsmentioning
confidence: 71%